2010
DOI: 10.5251/abjna.2010.1.6.1119.1125
|View full text |Cite
|
Sign up to set email alerts
|

Anthracnose disease response in the Burundi sorghum germplasm collection

Abstract: The United States National Plant Germplasm System maintains 151 sorghum accessions from Burundi of which 148 accessions were evaluated for resistance to Colletotrichum sublineolum at the Tropical Agriculture Research Station in Isabela, Puerto Rico in replicated evaluations during the 2007 and 2008 growing seasons. For the 2007 experiment, 120 accessions showed a resistant response with 89 of these accessions rated as resistant in 2008. The resistant accessions showed reddening of inoculated leaves with no ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Resistance can be inherited as a qualitative or quantitative trait (Mehta et al 2005;Mohan et al 2010) and extensive variation in disease response has been observed in populations developed to determine the genetics of resistance (Erpelding 2007); therefore, the diversity Numbers followed by the same letter were not significantly different at the 5% probability level 2 Disease severity for the susceptible accessions from the Ngamiland and Kgatleng was significantly different at the 10% probability level in disease response and overall lower disease severity would suggest genetic variation for host resistance. Additionally, quantitative resistance resulting in lower disease severities is frequently observed in sorghum landraces and disease response often shows regional specificity (Erpelding 2008(Erpelding , 2010Erpelding & Prom 2004) as was observed for the accessions from Botswana.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance can be inherited as a qualitative or quantitative trait (Mehta et al 2005;Mohan et al 2010) and extensive variation in disease response has been observed in populations developed to determine the genetics of resistance (Erpelding 2007); therefore, the diversity Numbers followed by the same letter were not significantly different at the 5% probability level 2 Disease severity for the susceptible accessions from the Ngamiland and Kgatleng was significantly different at the 10% probability level in disease response and overall lower disease severity would suggest genetic variation for host resistance. Additionally, quantitative resistance resulting in lower disease severities is frequently observed in sorghum landraces and disease response often shows regional specificity (Erpelding 2008(Erpelding , 2010Erpelding & Prom 2004) as was observed for the accessions from Botswana.…”
Section: Discussionmentioning
confidence: 99%
“…Disease infection and development is the highest in tropical and subtropical regions where high temperatures and humidity are common (Burrell et al, ; Crouch & Beirn, ; Marley, Diourte, Neya, & Rattunde, ; Mathur, Thakur Neya, Marley, & Casela, ; Mehta et al, ; Ngugi, King, Abayo, & Reddy, ; Patil et al, ). Sorghum anthracnose is widely reported in East Africa, including Kenya, Uganda and Ethiopia (Erpelding, ; Sserumaga, Biruma, Akwero, Okori, & Edema, ; Were & Ochuodho, ). In Ethiopia, the disease is one of the most important sorghum production constraints (Chala, Alemu, Prom, & Tronsmo, and Chala, Brurberg, & Tronsmo, ).…”
Section: Introductionmentioning
confidence: 99%
“…. Sorghum anthracnose is widely reported in East Africa, including Kenya, Uganda and Ethiopia (Erpelding, 2010;Sserumaga, Biruma, Akwero, Okori, & Edema, 2013;Were & Ochuodho, 2012). In Ethiopia, the disease is one of the most important sorghum production constraints (Chala, Alemu, Prom, &.…”
mentioning
confidence: 99%